¿Cómo funciona el mercado de energía eléctrica?, caracterización de la demanda de energía eléctrica en el sector residencial por estrato socioeconómico para Bogotá en el periodo comprendido entre 2005-2015 (2017)
The electric energy price structure in Colombia is formed from a scheme of subsidies and contributions that vary with the consumers` socioeconomic strata. In this work the demand for electric energy at the residential sector is characterized in order to establish the differences in price and income elasticities of demand for each strata and, in this way, to analyze the impact of electricity price and the average income of households on energy demand. We use data from the SUI and the DANE. The demand function is estimated using monthly data from 2005 to 2015. The results indicate that the price elasticities of energy demand is lower at the strata 1, 2 and 3 of Bogotá.